Airline Marketing Strategy with Low Cost Carrier Concept in Improving Company Competitiveness - Rumani, Daniel Dewantoro; Wardana, Miko Andi; Iswahyudi, Prasetyo; Luwihono, Andung (SAFE-Network, 2025)
This study investigates the influence of marketing strategies under the Low Cost Carrier model on the competitiveness of PT Lion Mentari Airlines, one of Indonesia’s leading budget airlines. As air travel becomes increasingly accessible, LCCs have emerged as key players in providing affordable and efficient transportation. This research adopts a qualitative descriptive approach to examine how four marketing variables pricing strategy, route accessibility, service simplification, and promotion strategy contribute to Lion Air’s competitive positioning in the domestic aviation industry. Data were collected through interviews, observations, and documentation involving marketing and operational personnel. The findings indicate that dynamic pricing, regional route expansion, simplified in flight services, and digital promotions collectively strengthen brand visibility, customer loyalty, and operational efficiency. These strategies allow Lion Air to serve broader market segments while maintaining profitability in a highly competitive environment. The study concludes that the integration of cost efficient marketing approaches under the LCC framework significantly enhances organizational competitiveness and sustainability. Implications of this study highlight the importance of strategic alignment between service design and market expectations in maintaining a resilient LCC business model.